Analytical methods for gelatin differentiation from bovine and porcine origins and food products. - Raja Nhari, Raja Mohd Hafidz; Ismail, Amin; Che Man, Yaakob (Wiley-Blackwell, 2012)
Usage of gelatin in food products has been widely debated for several years, which is about the source of gelatin that has been used, religion, and health. As an impact, various analytical methods have been introduced and developed to differentiate gelatin whether it is made from porcine or bovine sources. The analytical methods comprise a diverse range of equipment and techniques including spectroscopy, chemical precipitation, chromatography, and immunochemical. Each technique can differentiate gelatins for certain extent with advantages and limitations. This review is focused on overview of the analytical methods available for differentiation of bovine and porcine gelatin and gelatin in food products so that new method development can be established.